Protaetiibacter larvae sp. nov. and Agromyces intestinalis sp. nov., isolated from the gut of larvae of Protaetia brevitarsis seulensis, reclassification of Lysinimonas yzui as Pseudolysinimonas yzui comb. nov. and emended description of the genus Pseudolysinimonas. Issue 4 (29th April 2021) - Lee, Shin Ae; Heo, Jun; Kim, Mi Ae; Tamura, Tomohiko; Saitou, Satomi; Kwon, Soon-Wo; Weon, Hang-Yeon
Abstract : Two bacterial strains, FWR-8 T and CFWR-9 T, were isolated from the gut of larvae of Protaetia brevitarsis seulensis that were raised at the National Institute of Agricultural Sciences, Wanju-gun, Republic of Korea. Both strains were strictly aerobic, Gram-stain-positive and non-motile. Strain FWR-8 T possessed the highest sequence similarity (98.7 %) to that of Protaetiibacter intestinalis 2DFWR-13 T and the phylogenetic tree revealed that strain FWR-8 T formed a cluster with Ptb. intestinalis 2DFWR-13 T . Pseudolysinimonas kribbensis MSL-13 T and Lysinimonas yzui N7XX-4 T shared a high 16S rRNA gene sequence similarity (97.8 %) and formed a cluster adjacent to the cluster that included Ptb. intestinalis 2DFWR-13 T . The 16S rRNA gene sequence of strain CFWR-9 T exhibited the highest similarity (97.7 %) to that of Agromyces binzhouensis OAct353 T and the phylogenetic tree indicated that strain CFWR-9 T formed one independent cluster with A. binzhouensis OAct353 T that was within the radius of the genus Agromyces . The peptidoglycan type, major fatty acids, major menaquinones and total polar lipids of strain FWR-8 T were characterized as type B1, iso-C16 : 0, anteiso-C15 : 0 and anteiso-C17 : 0, MK-15, MK-16 and MK-14, and diphosphatidylglycerol, phosphatidylglycerol, two unidentified glycolipids and one unidentified lipid, respectively. Those from strain CFWR-9 T were type B1, iso-C16 : 0, anteiso-C15 : 0 and anteiso-C17 : 0, MK-11, MK-12 and MK-10, and diphosphatidylglycerol, phosphatidylglycerol, two unidentified glycolipids and one unidentified lipid, respectively. Based on the phenotypic and genotypic data, strains FWR-8 T and CFWR-9 T each represent a novel species within the genera Protaetiibacter and Agromyces, respectively. For these species, the names Protaetiibacter larvae sp. nov. and Agromyces intestinalis sp. nov. have been proposed, with the type strains FWR-8 T (=KACC 19322 T =NBRC 113051 T ) and CFWR-9 T (=KACC 19306 T =NBRC 113046 T ), respectively. Our results also justify a reclassification of Lysinimonas yzui as Pseudolysinimonas yzui comb. nov. and an emended description of the genus Pseudolysinimonas isprovided.